Analisis Jumlah Penyewaan Kamar Hotel Menggunakan Pentaho BI Berbasis Data Warehouse: ( Studi Kasus Hotel Grand Santhi ) - Pratama, I Putu Agus Eka; Antara, I Made Gede Sunia Pradnyantara (Prodi Sistem Informasi FST Universitas Jambi, 2020)
Analysis is one of the most important things done for companies to conduct performance evaluations in order to know the strengths and weaknesses contained in a company. Therefore, this study aims to make a report on the rental of hotel rooms for a month that is useful in determining the promotion of equal distribution of all types of hotel room lodging in a case study at the Grand Santhi Hotel located in Kota Denpasar, Bali. The solution of the existing problem is to use open source Pentaho BI to create reports that simplify analysis. The data will be created in a multi-dimensional design to facilitate the application of data warehouse design and system design that has been created.